Thermodynamic properties of selenoether-functionalized ionic liquids and their use for the synthesis of zinc selenide nanoparticles. Issue 14 (21st March 2018) - Klauke, Karsten; Zaitsau, Dzmitry H.; Bülow, Mark; He, Li; Klopotowski, Maximilian; Knedel, Tim-Oliver; Barthel, Juri; Held, Christoph; Verevkin, Sergey P.; Janiak, Christoph
Abstract : Predicting IL properties: Thermodynamically the Se atom in Se–ILs performs like a CH2 group, but chemically it reacts as a source of Se. Abstract : Three selenoether-functionalized ionic liquids (ILs) of N -[(phenylseleno)methylene]pyridinium (1 ), N -(methyl)- (2 ) and N -(butyl)- N '-[(phenylseleno)methylene]imidazolium (3 ) with bis(trifluoromethanesulfonyl)imide anions ([NTf2 ]) were prepared from pyridine, N -methylimidazole and N -butylimidazole with in situ obtained phenylselenomethyl chloride, followed by ion exchange to give the desired compounds. The crystal structures of the bromide and tetraphenylborate salts of the above cations (1-Br, 2-BPh4 and3-BPh4 ) confirm the formation of the desired cations and indicate a multitude of different supramolecular interactions besides the dominating Coulomb interactions between the cations and anions. The vaporization enthalpies of the synthesized [NTf2 ]-containing ILs were determined by means of a quartz-crystal microbalance method (QCM) and their densities were measured with an oscillating U-tube. These thermodynamic data have been used to develop a method for assessment of miscibility of conventional solvents in the selenium-containing ILs by using Hildebrandt solubility parameters, as well as for modeling with the electrolyte perturbed-chain statistical associating fluid theory (ePC-SAFT) method. Furthermore, structure–property relations between selenoether-functionalized and similarly shaped corresponding aryl-substituted imidazolium- and pyridinium-based ILs were analyzed and showed that the contribution of the selenium moiety to the enthalpy of vaporization of an IL is equal to the contribution of a methylene (CH2 ) group. An incremental approach to predict vaporization enthalpies of ILs by a group contribution method has been developed. The reaction of these ILs with zinc acetate dihydrate under microwave irradiation led to ZnSe nanoparticles of an average diameter between 4 and 10 nm, depending on the reaction conditions.